Identification of NPTX2 as a prognostic biomarker of Alzheimer's disease through a longitudinal CSF proteomics study in ADNI subjects: Developing topics. (7th December 2020) - Libiger, Ondrej; Shaw, Leslie M; Watson, Mark; Nairn, Angus C; Umaña, Kelly; Canet‐Avilés, Rosa M; Jack, Clifford R; Breton, Yannick‐André; Cortes, Laetitia; Chelsky, Daniel; Spellman, Daniel S; Baker, Susan; et al.
Abstract: Background: Many biomarkers have been identified which are relevant to studies of Alzheimer's disease (AD), especially pertaining to the evolution of amyloid plaque, tau tangle pathology and loss of brain tissue. There remains, however, the need for additional biomarkers that reflect pathologic processes affecting neuronal function during pre‐clinical and prodromal stages, to help accelerate drug development efforts. Method: A retrospective investigation of longitudinal changes in concentrations of five analytes (CgA, NPTX2, VGF, SCG2, FABP3) was performed in CSF of ADNI subjects. Rates of longitudinal change in these candidate proteins were compared between: a) Cognitively normal subjects (CN; n = 76) versus subjects with mild cognitive impairment (MCI; n = 111) at baseline; b) Subjects categorized as p‐Tau181 /Aβ1‐42 ratio positive versus negative at baseline; and c) 'Progressors', i.e., subjects who progressed from CN to MCI or MCI to Dementia within a predefined period versus subjects categorized as 'non‐progressors'. Following a pre‐specified analysis plan involving mixed‐effects linear models adjusting for relevant covariates, the association between changes in each analyte's concentration and subjects' clinical progression was quantified. Result: NPTX2, a protein involved in synaptic function, showed the strongest association with baseline clinical diagnosis of MCI, and a positive p‐Tau181 /Aβ1‐42 ratio – the biomarker profile indicative of AD. Differences in the rates of decline in NPTX2 concentration between subjects classified as CN and MCI as well as between p‐Tau181 /Aβ1‐42 ratio positive and negative subjects were highly significant (p=0.008 and p<0.0001 resp.), suggesting a complex interaction between the rate of decline in subjects at various stages along the disease continuum. Of the five analytes, only the rates of change in NPTX2 concentrations differed between progressors and non‐progressors (mean difference: 0.08 ± 0.02 ng/mL/year); p = 0.0004), further validating the association of changes in NPTX2 concentration and clinical prognosis. Additional exploratory analyses indicated the presence of a correlation between NPTX2 rates of change and declining cognition measured by MMSE (coef. = 0.3, p = 0.02), and Adas‐Cog 13 (coef. = ‐0.3, p = 0.01). Conclusion: These results suggest that NPTX2 concentration may serve as a prognostic biomarker of accelerated cognitive decline in at least a subset of individuals with AD.